Evaluation of Academic Supervision by The Principals of SDIT In Surakarta City in The Implementation of The Independent Curriculum (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Based on the 2024 Education Report, the quality of learning in Integrated Islamic Elementary Schools (SDIT) throughout Surakarta City shows significant variation. One important factor influencing this quality is the role of the principal, particularly in implementing academic supervision. This study aims to evaluate the implementation of academic supervision by SDIT principals in Surakarta City, within the context of the Independent Curriculum (IKM) Implementation. This study uses a descriptive quantitative approach. Data were collected through a questionnaire technique. The subjects of this study involved 153 teachers from 8 SDITs in Surakarta City. The results of content validation (Aiken's Validity) showed that the questionnaire was highly valid. The results of the CFA using the Jamovi application stated that the questionnaire had adequate construct validity and was in accordance with the structure of the theory being tested. The results of the questionnaire reliability estimation obtained a value ofAlpha Cronbach 0.949 (very high). The evaluation results of the implementation of academic supervision showed a very good level of success in all three aspects. The success rate in the planning aspect reached 86%, the implementation aspect 85%, and the goal achievement aspect reached 84%. The average success rate of academic supervision by the principals of Islamic Elementary Schools (SDIT) throughout Surakarta City at IKM reached 85% (very good).